Effect of losartan and benzbromarone on the level of human urate transporter 1 mRNA - Nindita, Yora; Hamada, Toshihiro; Bahrudin, Udin; Hosoyamada, Makoto; Ichida, Kimiyoshi; Iwai, Chisato; Urashima, Sunao; Kuwabara, Masanari; Utami, Sulistiyati Bayu; Mizuta, Einosuke; Yamada, Kensaku; Igawa, Osamu; Shigemasa, Chiaki; Ninomiya, Haruaki; Tsuchihashi, Takuya; Hisatome, Ichiro (Arzneimittelforschung, 2010)
Both an angiotensin II receptor blocker, losartan (CAS 124750-99-8) and a serum urate lowering agent, benzbromarone (CAS 3562-84-3) exert a uricosuric action by inhibiting urate transporter 1 (URAT1). A recent clinical trial indicated that losartan could reduce the level of serum urate in hypertensive patients treated with urate lowering agents, suggesting the different mode of action of losartan from benzbromarone. In the present study, the effect of losartan and benzbromarone on the level of URAT1 mRNA was determined in transfected HEK293 cells. Losartan caused a significant reduction of its mRNA level, whereas it was not affected by benzbromarone. These results indicate that losartan decreases the level of human URAT1 mRNA, which may underlie the uricosuric action of losartan in hypertensive patients treated with serum urate lowering agents.
Keywords: Benzbromarone; CAS 3562-84-3; CAS 124750-99-8; Human urate transporter 1 mRNA; Losartan